2011
DOI: 10.1007/s10152-011-0254-3
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Tigriopus (Copepoda, Harpacticoida, Harpacticidae) from Thailand with the description of its naupliar development

Abstract: Both genders of Tigriopus thailandensis sp. nov. are described from a laboratory stock raised from individuals collected from the seaweed Enteromorpha clathrata in Thailand (Bangsaen Beach, Chonburi Province). Tigriopus thailandensis sp. nov. shares with its closest relative T. japonicus Mori, 1932 two setae on the third exopodal segment of leg 4 while other congeners bear 3 inner setae. However, allobasis and exopod of antenna in both genders are much more slender and elongate than in T. japonicus. All six na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…As the expansion of mariculture has become increasingly important as a means to meet the protein supply for human consumption, the development of novel technologies for fish farming is urgently needed (Camus & Zeng ; Chullasorn, Ivanenko, Dahms, Kangtia & Yang ). In aquaculture hatcheries, the use of live food is essential for successful larval fish rearing.…”
Section: Introductionmentioning
confidence: 99%
“…As the expansion of mariculture has become increasingly important as a means to meet the protein supply for human consumption, the development of novel technologies for fish farming is urgently needed (Camus & Zeng ; Chullasorn, Ivanenko, Dahms, Kangtia & Yang ). In aquaculture hatcheries, the use of live food is essential for successful larval fish rearing.…”
Section: Introductionmentioning
confidence: 99%
“…In the Atlantic–Mediterranean area (i.e., the Mediterranean Sea and the Eastern Atlantic Ocean south to the Tropic of Cancer), three Tigriopus species are to date allegedly reported to occur: Tigriopus fulvus , T. brevicornis , and T. brachydactylus Candeias, 1959. However, T. brachydactylus was actually erroneously reported to occur in Northern Europe by Chullasorn et al (2011) and Chullasorn et al (2013), whereas, as already evidenced by Park et al (2014), the species was originally described from Angola (western coast of Southern Africa) and never reported for European coasts. Moreover, T. minutus Božić, 1960 was described just south of our study area, and reported to occur in Senegal (Božić, 1960).…”
Section: Introductionmentioning
confidence: 95%